Ethanol consumption synergistically increases ultraviolet radiation induced skin damage and immune dysfunction. Issue 1 (January 2021) - Brand, Rhonda M.; Stottlemyer, John Mark; Paglia, Melissa C.; Carey, Cara Donahue; Falo, Louis D.
Highlights: Mouse models containing both EtOH abuse and UV exposure induces synergistic immune suppression. Dual EtOH and UV synergistically amplify immune dysfunction and local skin damage. Skin changes induced by UV combined with EtOH are consistent between mice and humans. Results support epidemiological correlations between EtOH use and skin cancer. Provides basis for education about dangers of combining excess EtOH and UV exposure. Abstract: Background: Excessive UV radiation disrupts skin homeostasis by multiple mechanisms that extend beyond the simple erythema associated with sunburns including reduction of antioxidants, increased DNA damage, and impairment of skin immune responses. Recreational UV exposure frequently occurs concurrently with excessive ethanol (EtOH). Epidemiological studies suggest a harmful, dose-dependent impact of EtOH in the setting of high UV exposure, leading to increased severity of sunburns relative to those generated in the absence of EtOH. Furthermore, EtOH consumption and UV radiation have multiple overlapping effects on the skin that could account for the epidemiological association. Objective: To elucidate the relationship between excessive EtOH ingestion and UV exposures on early skin damage and downstream immune dysfunction. Methods: We examined the impact of UVB on local skin damage, including inflammation, sunburned cells, apoptotic cells, melanin and antioxidant levels, DNA damage and immune dysfunction in the presence or absence of EtOH ingestion by combining standard mouse models of EtOH consumption and UVB exposure models. To confirm that the observed changes in mouse skin were relevant to human skin, we investigated the effects of EtOH on UV-induced skin damage with human skin explants. Results: We demonstrated that EtOH consumption and UV exposure act synergistically to increase the severity of local skin damage resulting in impaired melanin responses, reduced antioxidants, greater DNA damage, and immune dysfunction as measured by reduced contact hypersensitivity. Conclusions: The results support incorporation of the risks of combined UV exposure and excessive alcohol consumption into public health campaigns.